In vitro studies on CAD/CAM restorations fabricated with Procera technology: an overview - Karl, Matthias (Quintessence International, 2015)
The number of available CAD/CAM systems has dramatically increased in recent years. Consequently, although clinical data for the newer systems are missing, in vitro studies are published frequently. The goal of this review was to provide an overview of in vitro studies conducted with the Procera system.Repeated online searching in PubMed was done until June 2014 using the search terms Nobel, Procera, dental, implant. Papers reporting clinical studies, evaluating cementation procedures as well as investigations using norm-shaped test specimens were excluded from analysis. Data were then assigned to the following categories: material characterization, scanner technology, single crown and multi-unit restorations, passivity of fit of implant-supported restorations, and implant abutments.Relative comparisons within specific studies based on the control specimens used indicate that all Procera restorations meet clinical requirements. Absolute comparisons between studies are not possible due to great variations in study design and outcome measures.While the relevance of in vitro data is frequently questioned, practicing clinicians have to rely on such information when judging the applicability of a novel CAD/CAM system. Given that the Procera CAD/CAM system has proven its reliability both in vitro and in clinical use, existing in vitro data for this CAD/CAM system may serve as a useful reference providing benchmark values for future developments.
EVALuna2:24821